Generation of skeletal muscle cells from pluripotent stem cells: advances and challenges - Abujarour, Ramzey; Valamehr, Bahram (Frontiers in Cell and Developmental Biology, 2015)
Human pluripotent stem cells (hPSCs) possess unlimited proliferative potential while maintaining the ability to differentiate into any cell type including skeletal muscle cells (SMCs). hPSCs are amenable to genetic editing and can be derived from patient somatic cells, and thus represent a promising option for cell therapies for the treatment of degenerative diseases such as muscular dystrophies. There are unresolved challenges however associated with the derivation and scale-up of hPSCs and generation of differentiated cells in large quantity and high purity. Reported myogenic differentiation protocols are long, require cell sorting and/or rely on ectopic expression of myogenic master regulators. More recent advances have been made with the application of small molecules to enhance the myogenic differentiation efficiency and the identification of more selective markers for the enrichment of myogenic progenitors with enhanced regenerative potential. Here we review the field of myogenic differentiation and highlight areas requiring further research.